2019
DOI: 10.3390/f10070550
|View full text |Cite
|
Sign up to set email alerts
|

Soil Depth Determines the Composition and Diversity of Bacterial and Archaeal Communities in a Poplar Plantation

Abstract: Understanding the composition and diversity of soil microorganisms that typically mediate the soil biogeochemical cycle is crucial for estimating greenhouse gas flux and mitigating global changes in plantation forests. Therefore, the objectives of this study were to investigate changes in diversity and relative abundance of bacteria and archaea with soil profiles and the potential factors influencing the vertical differentiation of microbial communities in a poplar plantation. We investigated soil bacterial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 58 publications
13
31
0
Order By: Relevance
“…Within one‐meter soil profiles, the species richness (OTU number) decreased significantly with increasing soil depth (Figure ). This trend of decreasing microbial alpha diversity is consistent with many other previous studies (Deng et al, 2015; Feng et al, 2019; Tang et al, 2018), which have shown that the richness, abundance, and composition of the soil microbiome displayed layer specificity and distinct differences across strata. The community distance showed clearly that community variability increased within sites from Upper layer to Substratum (Figure ), suggesting community heterogenization was occurring.…”
Section: Discussionsupporting
confidence: 92%
“…Within one‐meter soil profiles, the species richness (OTU number) decreased significantly with increasing soil depth (Figure ). This trend of decreasing microbial alpha diversity is consistent with many other previous studies (Deng et al, 2015; Feng et al, 2019; Tang et al, 2018), which have shown that the richness, abundance, and composition of the soil microbiome displayed layer specificity and distinct differences across strata. The community distance showed clearly that community variability increased within sites from Upper layer to Substratum (Figure ), suggesting community heterogenization was occurring.…”
Section: Discussionsupporting
confidence: 92%
“…Our PCR analyses of soil samples (0–15 cm depth) failed to detect the presence of methanogens in the shallow soil, consistent with our measurements of methane uptake only at the soil surface (Fig. 4), and previous reports of minimal Euryarchaeota DNA in poplar forest soils (Feng et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the bacterial and fungal communities differ depending on soil depth (topsoil versus subsoil) over long-term fertilization studies ( Gu et al, 2017 ). Many studies have shown that the microbial diversity typically decreases with soil depth, probably owing to the decreased exposure to fertilizers from topsoil to subsoil ( Li et al, 2014 ; Feng et al, 2019 ). Sampling of bulk soil can introduce high variability and, therefore, it is important to take into consideration sampling strategies to account for this variability ( Ogram et al, 2007 ).…”
Section: Limitations Of Microbial Community Experiments and Their Appmentioning
confidence: 99%